Association between dietary calcium intake and constipation in a metabolic syndrome population: evidence from NHANES 2005–2010 - Zhu, Li; Yang, Long; Liang, Zonghua; Shi, Wen; Ma, Ming; Chen, Jingbo; Abdula, Zulipikaer; Gong, Xuchen (Frontiers in Nutrition, 2024)
Background The global prevalence of Metabolic Syndrome (MetS) is increasing, primarily characterized by abdominal obesity, which significantly heightens the risk of cardiovascular diseases, gastrointestinal disorders, and cancers. Constipation is a common gastrointestinal issue that impacts both physiological and psychological health and worsens with age. Calcium, an essential mineral vital for human health, has been proven to be crucial not only for bone health but also beneficial for gastrointestinal health. However, the results regarding its impact on constipation are inconsistent. This study aimed to investigate the relationship between dietary calcium intake and constipation in individuals with MetS. Methods This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2010. Participants were assessed for MetS based on the International Diabetes Federation (IDF) criteria. Dietary calcium intake was evaluated through 24-h dietary recalls, and constipation was defined based on the frequency of bowel movements recorded in the bowel health questionnaire. The relationship between calcium intake and constipation was explored using logistic regression models with adjustment for covariates, and restricted cubic spline analyses were also used to investigate nonlinear relationships. Results The study included 4,838 adult participants with MetS. Adjusted logistic regression revealed that an increase in dietary calcium intake was significantly associated with a reduced risk of constipation (OR: 0.562, 95% CI: 0.379 to 0.835, p = 0.006). Compared to the lowest quartile, the highest quartile of dietary calcium intake significantly decreased the risk of constipation (OR: 0.282, 95% CI: 0.115 to 0.691, p = 0.008). Results from the restrictive cubic spline analysis indicated a negative linear association between dietary calcium intake and constipation risk (non-linearity p = 0.704). Conclusion The findings suggested that increased dietary calcium intake is associated with a decreased risk of constipation among MetS patients, emphasizing dietary calcium as a potentially modifiable factor for managing gastrointestinal symptoms in this population.